2020
DOI: 10.1021/acs.langmuir.0c00427
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Bubble and Oil Repellency of Biomimetic Pincushion and Plastron-Like Honeycomb Films

Abstract: Underwater highly bubble and oil-repellent surfaces were prepared based on honeycomb- and pincushion-structured films prepared by breath figure technique and post modifications including UV-ozone treatment and peeling the top layer. Furthermore, bubble generation from the plastron-like honeycomb gas chamber by attaching oil droplet onto the surface of honeycomb films was first observed. Both controlling gas bubbles and oil droplets underwater are important issues in the field of microfluidics since they are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…When the contact angle of oil droplets in water was measured on untreated PB HC films or on films subjected to UV-O 3 treatment for 30 min or less, the oil droplet size gradually decreased and they were absorbed by the film after oil droplets were attached to the surface. Consistent with the results reported in our previous paper, [30] the water-repellent PB HC film was not wetted with water and an air layer was maintained in its pores. The pores of the HC film are connected by transverse holes, which enable the oil droplets to be absorbed by the volume of the pores.…”
Section: Wwwadvmatinterfacesdesupporting
confidence: 92%
See 2 more Smart Citations
“…When the contact angle of oil droplets in water was measured on untreated PB HC films or on films subjected to UV-O 3 treatment for 30 min or less, the oil droplet size gradually decreased and they were absorbed by the film after oil droplets were attached to the surface. Consistent with the results reported in our previous paper, [30] the water-repellent PB HC film was not wetted with water and an air layer was maintained in its pores. The pores of the HC film are connected by transverse holes, which enable the oil droplets to be absorbed by the volume of the pores.…”
Section: Wwwadvmatinterfacesdesupporting
confidence: 92%
“…The sudden decrease of the contact angle after 45 min of UV–O 3 treatment is attributed to the capillary force of the pore structure, which causes water droplets to spread through the pores when the contact angle is less than 90°. [ 30 ] The θ o/a increased slightly after 15 min of treatment; however, after that, the droplets almost spread. These results indicate that the introduction of surface functional groups by UV–O 3 treatment imparted the HC films with amphiphilic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassie type wetting was observed on the surface comprising porous surfaces containing air layers beneath the water, and Wenzel type modeled the wetting state when the water wetted the whole surfaces. As reported in the previous report, 30 min irradiation of UV–O 3 made the surfaces hydrophilic, but they show still Cassie type wetting property; in other words, the air was trapped inside of the honeycomb structure since the UV–O 3 hydrophilized the top surface of the honeycomb, films but bottom surfaces of the pores were still hydrophobic. This made the silica-coated honeycomb film still hydrophobic.…”
Section: Resultssupporting
confidence: 66%
“…Bormashenko et al also reported the wettability control on the porous films prepared by the breath figure technique . In order to pattern hydrophobic and hydrophilic regions on the surface of honeycomb films, UV–O 3 treatment has been employed to oxidize the surface of polymers. , This process allows formation of surface chemical patterns to control wettability; however, it degrades the polymers and makes the honeycomb films mechanically fragile and chemically unstable. In order to realize wettability patterning without mechanical and chemical degradation, a new approach is required.…”
Section: Introductionmentioning
confidence: 99%